Humoral immune responses in different stages of wound healing in Black Bengal goats (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The current study was carried out to assess the humoral immune responses according to age at different stages of wound healing in Black Bengal goats (BBG). Materials and Methods: Apparently, healthy BBGs (n = 20) were collected and divided into five groups based on their age: Group A (control, 3 years), Group B (3 to 5 years), Group C (2 to